2017
DOI: 10.1016/j.proci.2016.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the chemical structures of laminar premixed flames fueled by acetaldehyde

Abstract: Acetaldehyde is a key intermediate formed during the combustion of hydrocarbon and oxygenated fuels, and its role as an air pollution is concern-arousing. A better understanding of its combustion characteristics is of significance in developing core mechanisms and reducing the associated emissions. In this work, chemical structures of low-pressure laminar premixed acetaldehyde flames with equivalence ratios of 1.7 and 1.0 were measured by employing molecular-beam mass spectrometry with synchrotron vacuum ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Taatjes et al [17,18] investigated many hydrocarbon flames depicting most of the chemical classes and concluded that in the low pressure hydrocarbon flames, the major source of enols is through reactions of alkenes with OH. Since then, various studies reported ethenol formation in hydrocarbons and various oxygenated fuels [14,[19][20][21][22][23][24][25][26]. The consumption of ethenol can be through direct and/or radical-catalyzed tautomerization forming acetaldehyde or through decomposition forming other products.…”
Section: Ethylene Glycol -Reaction Kineticsmentioning
confidence: 99%
“…Taatjes et al [17,18] investigated many hydrocarbon flames depicting most of the chemical classes and concluded that in the low pressure hydrocarbon flames, the major source of enols is through reactions of alkenes with OH. Since then, various studies reported ethenol formation in hydrocarbons and various oxygenated fuels [14,[19][20][21][22][23][24][25][26]. The consumption of ethenol can be through direct and/or radical-catalyzed tautomerization forming acetaldehyde or through decomposition forming other products.…”
Section: Ethylene Glycol -Reaction Kineticsmentioning
confidence: 99%
“…• CHOH → CH 3 CHO) can explain the high concentrations of formaldehyde and acetaldehyde [24]. As proposed by Tao et al [25], the degradation of acetaldehyde can result in the formation of CH 3…”
Section: Engine Resultsmentioning
confidence: 86%
“…In the end, due to the huge differences observed during the research, the authors recommended the need for new experimental and detailed numerical studies. Tao et al [145] reported nearly 40 species in laminar and premixed flames of acetaldehyde. Christensen et al [146] studied the laminar burning velocities at atmospheric pressure and different initial temperatures.…”
Section: Light Aldehydesmentioning
confidence: 99%